Clearance of Gram-Negative Bacterial Pathogens from the Ocular Surface by Predatory Bacteria - Eric G. Romanowski; Shilpi Gupta; Androulla Pericleous; Daniel E. Kadouri; Robert M. Q. Shanks (MDPI AG, 2021)
It was previously demonstrated that predatory bacteria are able to efficiently eliminate Gram-negative pathogens including antibiotic-resistant and biofilm-associated bacteria. In this proof-of-concept study we evaluated whether two species of predatory bacteria, Bdellovibrio bacteriovorus and Micavibrio aeruginosavorus, were able to alter the survival of Gram-negative pathogens on the ocular surface. Clinical keratitis isolates of Pseudomonas aeruginosa (strain PAC) and Serratia marcescens (strain K904) were applied to the ocular surface of NZW rabbits followed by application of predatory bacteria. At time intervals, surviving pathogenic bacteria were enumerated. In addition, B. bacteriovorus and S. marcescens were applied to porcine organ culture corneas under contact lenses, and the ocular surface was examined by scanning electron microscopy. The ocular surface epithelial layer of porcine corneas exposed to S. marcescens, but not B. bacteriovorus was damaged. Using this model, neither pathogen could survive on the rabbit ocular surface for longer than 24 h. M. aeruginosavorus correlated with a more rapid clearance of P. aeruginosa but not S. marcescens from rabbit eyes. This study supports previous evidence that predatory bacteria are well tolerated by the cornea, but suggest that predatory bacteria do not considerably change the ability of the ocular surface to clear the tested Gram-negative bacterial pathogens from the ocular surface.